2012
DOI: 10.1371/journal.pone.0037874
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-Deep Pyrosequencing Detects Conserved Genomic Sites and Quantifies Linkage of Drug-Resistant Amino Acid Changes in the Hepatitis B Virus Genome

Abstract: BackgroundSelection of amino acid substitutions associated with resistance to nucleos(t)ide-analog (NA) therapy in the hepatitis B virus (HBV) reverse transcriptase (RT) and their combination in a single viral genome complicates treatment of chronic HBV infection and may affect the overlapping surface coding region. In this study, the variability of an overlapping polymerase-surface region, critical for NA resistance, is investigated before treatment and under antiviral therapy, with assessment of NA-resistant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
41
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 51 publications
7
41
0
1
Order By: Relevance
“…Wild-type HBV samples would inherently have sequence variants, and the detection of rare reads could affect interpretation (normal variants versus the intrinsic error rate of NGS). Use of the plasmid control avoids this potential interpretation bias (8,10). The error rate of NGS has been estimated to be Ͻ0.05%, with conservative cutoffs of 1% (8,24), which has been within the observed results of this HBV NGS assay for resistance and genotyping (Ͻ0.1%).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Wild-type HBV samples would inherently have sequence variants, and the detection of rare reads could affect interpretation (normal variants versus the intrinsic error rate of NGS). Use of the plasmid control avoids this potential interpretation bias (8,10). The error rate of NGS has been estimated to be Ͻ0.05%, with conservative cutoffs of 1% (8,24), which has been within the observed results of this HBV NGS assay for resistance and genotyping (Ͻ0.1%).…”
Section: Discussionmentioning
confidence: 70%
“…As a result, there are significant limitations with the most commonly utilized methods for identifying HBV resistance: Sanger sequencing (relatively poor sensitivity and only detects consensus populations of Ͼ20%) and line-probe hybridization assays (unable to detect novel point mutations and susceptible to hybridization errors) (8). Ultradeep pyrosequencing (a method of next-generation sequencing [NGS]) can overcome these limitations with improved sensitivity to detect mutations, the ability to quantitate the presence of minor viral subpopulations, and the capability to identify novel resistance mutations (7)(8)(9)(10)(11).…”
mentioning
confidence: 99%
“…It has been reported previously that insertions and deletions are the most common types of errors in pyrosequencing and occur mainly in homopolymeric regions, where linear relationships between signal intensity and the number of incorporated nucleotides are no longer preserved (9). Several independent studies suggested miscellaneous cutoff values and in-house probabilistic algorithms to reduce noise; these cutoff values are generally low, ranging from 0.03% to 0.21% (15,20,39). In our study, we applied quality control criteria to reduce noise, based on quality scores or on properties of the reads, and we used a threshold (Ն1.0%) for detection of high-confidence variants for the purpose of focusing on the most significant variations.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the relationship between phenotypic features of the viral population and its genetic structure will help us study the pathogenicity of virus infection and may lead to therapeutic discoveries. Currently, a few applications of UDPS in HBV research have characterized genetic HBV sequence variations (17)(18)(19)(20), but none has focused on the HBV quasispecies complexity within the entire RT region on the basis of a data set derived with the UDPS technique. Furthermore, few studies have explored the difference in performance in the analysis of HBV RT gene heterogeneity with the clone-based sequencing (CBS) and NGS methods.…”
mentioning
confidence: 99%
“…Günümüzde HBV antiviral ilaç direncini belirlemede kullanılan genotipik yöntemler arasında dizi analizi, PCR-RFLP (Restriction fragment length polymorphism) ve ters hibridizasyon (Line probe, Lipa DR) yöntemi bulunmaktadır (12,13) . Antiviral direnci belirlemede doğru-dan dizi analizi ile ters hibridizasyon yöntemleri en yaygın kullanılan yöntemlerdir.…”
Section: Introductionunclassified